The Accentuation of the Earliest Latin Loanwords in Slavic - Matasović, Ranko (2005)
The earliest Latin loanwords in Proto-Slavic belong to the accentual paradigm A, if they are feminine, and to AP B, if they are masculine. There are none that belong to AP C ; it is argued that these loanwords must have entered Slavic before the operation of Dybo's law.
Projekt MZOS
ENG